بناء برنامج تعليمي مقترح قائم على التغيرات المناخية في مقرر الجغرافيا - بنت مصلح الأنصاري, وداد (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى بناء برنامج تعليمي مقترح قائم على التغيرات المناخية في مقرر الجغرافيا، وقياس فاعليته في تنمية التحصيل المعرفي للمفاهيم المناخية والوعي المناخي لدى طالبات المستوى الخامس الثانوي في مدينة مكة المكرمة. ولتحقيق ذلك تم اختيار عينة عشوائية متيسرة بلغت (30) طالبة من مجتمع الدراسة في الفصل الدراسي الثاني 2018/2019م. واتبعت الدراسة المنهج شبه التجريبي– تصميم المجموعة الواحدة. وجمعت بيانات الدراسة باستخدام ثلاث أدوات، وهي: اختبار التحصيل المعرفي، ومقياس الوعي، وأسئلة المقابلة شبه المقننة، وذلك بعد التأكد من صدقهما وثباتهما. وحُللت البيانات بالأساليب الإحصائية الوصفية والاستدلالية المناسبة باستخدام برنامج الحزمة الاحصائية للعلوم الاجتماعية كما حللت باستخدام الأساليب النوعية المناسبة. وكشفت نتائج الدراسة عن وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0,01 ≤ α) بين متوسطي درجات مجموعة الدراسة في التطبيقين القبلي والبعدي في اختبار التحصيل المعرفي لمفاهيم التغيرات المناخية، وفي مقياس الوعي المناخي لصالح التطبيق البعدي. أيضا كشفت النتائج عن تأثير كبير للبرنامج التعليمي في تنمية التحصيل المعرفي لمفاهيم التغيرات المناخية والوعي بها لدى العينة حيث بلغ معامل التأثير للمتغيرين المعتمدين(0,93،0,73)على التوالي، ووصل معامل بلاك للكسب المعدل للمتغيرين المعتمدين (1,30%،1,32%)على التوالي مما يدل على فاعلية عالية مقبولة للمتغيرين الأول والثاني للبرنامج التعليمي. واظهرت النتائج وجود علاقة ارتباطية موجبة طردية قوية بلغت (0,699) عند مستوى الدلالة (0,01 ≤α) بين المتغيرين المعتمدين مفاهيم التغيرات المناخية والوعي بها، كما اظهرت النتائج وجود علاقة تنبؤيه خطية لقيمة بيتا بلغت (0,3860,399) عند مستوى الدلالة (0,01 ≤α) على التوالي بين المتغيرين المعتمدين مفاهيم التغيرات المناخية والوعي بها في رفع كل منهما لمستوى الآخر. وأكدت نتائج المقابلة شبة المقننة النتائج الكمية للدراسة. وبناءً على نتائج الدراسة؛ قدمت مجموعة من التوصيات والمقترحات ذات الصلة. Abstract: The purpose of this study was to Building a proposed educational program based on climate changes in the geography course،and measuring its effectiveness in developing cognitive achievement of climate concepts and climate awareness among fifth-level secondary school students in the holy city of Makkah. To achieve this،an available random sample of (30) students from the study population was selected in the second semester of 2018/2019. The study followed the qui-experimental approach - one group design. The study data were collected using three tools،namely: the cognitive achievement test،the scale،and the semi-standardized interview data. The instruments were checked for validity and reliability. The study data were analyzed by descriptive and inferential statistic using SPSS. It is also analyzed using appropriate qualitative methods. The results of the study revealed that there are statistically significant differences at the level of significance (α ≤ 0,01) between the mean scores of the study group in the pre and post applications in the cognitive achievement test of the concepts of climate change. And in the climate awareness scale in favor of the post application،Also،the results for a significant educational impact on the development of concepts of oceanic growth and awareness of them are higher scores for the coefficient of impact coefficient approved (0,93,0,73)،respectively. The Black coefficient of the two independent variables were (1.32،1. 30) respectively،and this mean accepted effectiveness for the first variable and high effectiveness for the second variable. Also،the study finding revealed strong statistically correlations significant (0.699) at the level of significance (a≤0.01) between Climate concepts and awareness،in addition to a liner predictive correlations (0.386،0.399) respectively at the level of significance (a≤0.01) between the two independent variables t Climate concepts and awareness in raise one to other level. Based on the findings of the study،a set of relevant recommendations were suggested.
مقال
Keywords: بناء برنامج تعليمي، فاعلية، مفاهيم التغيرات المناخية، الوعي المناخي، الجغرافيا، المستوى الخامس الثانوي; build educational program; the effectiveness; concepts of climate change; climate awareness; geography; fifth level secondary.